Spiders 2 - Hoban, Steve; Hall, Karen Lee; Fawcett, John (USA : Copper Heart Entertainment, 2001)
An assault team storms a dive boat and kidnaps the crew before blowing up the boat. the next day we find Jason and Alexandra Paulson relaxing on their sailboat when they see the remains of the dive boat. They find a charred body on board. A strom hit and they are washed overboard and their sailboat sinks. A cargo ship rescues them. On board they meet Captain Bigelow, and Jason is treated by a Dr. Grbac. That night Jason's wheeled into a medical lab and experimented upon. Inside the lab he sees thousands of tiny spiders in a cage as well as huge mutant spiders! He soon learns that Dr. Grbac extracts DNA from spiders and injects it into human hosts. Spiders are immune to all going diseases from the common cold to cancer. He is going to patent his technique and make billions. Their attempt to escape becomes one huge horrifying nightmare when they accidentally released those giant spiders kept in into doctor's lab.
Editor, Brett Sullivan ; writer Karen Walton ; director of photography, Thom Best
Keywords: Animal in motion pictures